2022
DOI: 10.3390/v14122642
|View full text |Cite
|
Sign up to set email alerts
|

African Swine Fever Virus Exhibits Distinct Replication Defects in Different Cell Types

Abstract: African swine fever virus (ASFV) causes one of the most devastating diseases affecting pigs and wild suids, a worldwide epizootic situation exacerbated in recent years due to the lack of vaccine or effective treatment. ASFV has a restricted cell tropism, and is prone to replicate in porcine monocytes and alveolar macrophages with high efficiency. Here, the replication capabilities of ASFV were examined in swine pulmonary alveolar macrophages (PAMs) and compared with 3D4/21, PK−15, MA−104 and Marc−145 cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Suitable in vitro systems for the detection, isolation, and manipulation of field isolates of pathogenic ASFV are only available for porcine primary macrophages and monocytes derived from peripheral blood or other tissues (Meloni et al, 2022 ). The quality of primary cell preparations may vary from batch to batch due to differences in the health of donor animals and preparation techniques, and the generation of primary macrophages is time-consuming and expensive and can result in contamination leading to cell waste (Gao et al, 2022 ). Moreover, using primary cells to produce large-scale vaccines is ethically challenging and, therefore, not feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suitable in vitro systems for the detection, isolation, and manipulation of field isolates of pathogenic ASFV are only available for porcine primary macrophages and monocytes derived from peripheral blood or other tissues (Meloni et al, 2022 ). The quality of primary cell preparations may vary from batch to batch due to differences in the health of donor animals and preparation techniques, and the generation of primary macrophages is time-consuming and expensive and can result in contamination leading to cell waste (Gao et al, 2022 ). Moreover, using primary cells to produce large-scale vaccines is ethically challenging and, therefore, not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using primary cells to produce large-scale vaccines is ethically challenging and, therefore, not feasible. Consequently, the development of safe and effective ASFV vaccines and diagnosis has been hampered by the lack of continuous cell lines suitable for ASFV isolation and propagation (Gao et al, 2022 ; Masujin et al, 2021 ). In light of these obstacles, the development of sustainable cell lines susceptible to ASFV infection is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 3D4/21 can support the growth of cell-adapted ASFV-Lisbon 61 and field isolate Lillie SI/85 [ 31 , 32 ], but it was unable to maintain replication of the genotype II ASFV-HLJ/18 strain [ 33 ]. However, a more recent study showed that the ASFV genotype II strain CN/GS/2018 can attach and enter 3D4/21 cells, resulting in genome replication rate of up to 10 6 copies/mL [ 34 ]. Our result is consistent with this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 3D4/21 can support the growth of celladapted ASFV-Lisbon 61 and field isolate Lillie SI/85 [30,31], but was unable to maintain replication of the genotype II ASFV-HLJ/18 strain [32]. However, a more recent study showed that the ASFV genotype II strain CN/GS/2018 can attach and enter into 3D4/21 cells and proceed to genome replication up to 10 6 copies/ml [33]. Our result is consistent with this study.…”
Section: Discussionmentioning
confidence: 99%